Coping behavior in women with alopecia: its role in the development of psychological maladjustment and its association with disease genesis - Chemerys Мар’яна; Markova Маріанна (Psychosomatic Medicine and General Practice, 2026)
Background. Coping behavior is a key mechanism of mental adaptation in patients with alopecia; however, its relationship with disease genesis and level of maladjustment remains insufficiently studied. Objective. To investigate coping strategies in women with alopecia of different genesis and their association with the level of psychological maladjustment. Methods. A total of 153 women with alopecia (metabolic – 45, mixed – 108) were examined using the Ways of Coping Questionnaire. Comparative and correlational analyses were performed. Results. Patients with metabolic alopecia demonstrated a predominance of adaptive coping strategies (problem-solving, seeking social support), whereas patients with mixed alopecia showed higher levels of maladaptive coping (avoidance, distancing). Increasing maladjustment was associated with a shift from adaptive to maladaptive coping strategies. Conclusions. Coping behavior is a significant predictor of mental maladjustment in alopecia and represents a potential target for personalized psychotherapeutic interventions. Keywords: alopecia, coping behavior, mental maladjustment, anxiety, depression, stress, psychodermatology. УДК 616.891:616-052:615.851